Invariable Ribosome Stoichiometry During Murine Erythroid Differentiation: Implications for Understanding Ribosomopathies - Papagiannopoulos, Christos I.; Kyritsis, Konstantinos A.; Psatha, Konstantina; Mavridou, Dimitra; Chatzopoulou, Fani; Orfanoudaki, Georgia; Aivaliotis, Michalis; Vizirianakis, Ioannis S. (Frontiers in Molecular Biosciences, 2022)
Structural heterogeneity and specialization of ribosomes represents, an emerging, yet debatable, mechanism of gene expression regulation with a purported role in ribosomopathies, a group of disorders caused by mutations in ribosomal protein genes (RPs). Ribosomopathies mysteriously relate with tissue- specific symptoms (mainly anemia and frequently cancer predisposition), despite the ubiquitous expression of the associated RPs. An outstanding question that may shed light into disease pathogenicity and provide potential pharmacological interventions, is whether and how the ribosomal structure is modified during, the highly affected by RP mutations, erythroid differentiation. To address this issue, we analyzed ribosome structure and evolution using an established model of erythroid differentiation, through sucrose gradient ultracentrifugation and quantitative proteomics. We found that differentiation associated with an extensive reprogramming of the overall ribosomal levels, characterized by an increase in monosomes and a decrease in polysomes. However, by calculating a stoichiometry score for each independent ribosomal protein, we found that the main ribosomal structure remained invariable between immature and differentiated cells. In total, none of the 78 Ribosomal Proteins (RPs- 74 core RPs, Rack1, Fau and 2 paralogs) detected was statistically different between the samples. This data was further verified through antibody-mediated quantification of 6 representative RPs. Moreover, bioinformatic analysis of whole cell proteomic data derived out of 4 additional models of erythropoiesis revealed that RPs were co-regulated across these cell types, too. In conclusion, ribosomes maintain an invariant protein stoichiometry during differentiation, thus excluding ribosome heterogeneity from a potential mechanism of toxicity in ribosomopathies and other erythroid disorders.